Enhancing the Skills of Community First Responders (CFR) as The Frontline for Emergency Assistance Through Simulation Training - Widodo Widodo; Sumardino Sumardino; Sumardiyono Sumardiyono; Rendi Editya Darmawan (JENDELA NURSING JOURNAL, 2022)
Background: incidence of emergency case in community increase quickly. The (Community First Responders) CFR competence in implementing emergency algorythm as the first responder out of hospital is very important.Purpose: to discribe the CFR competence in implementing emergency algorythm after following simulation training.Methods: pre experimental without control group design with was chosen with the pre and post-test conducted on February 2021 to CFR in Surakarta Central Java, Indonesia. This study used consecutive sample of 222 CFR. The CFR was asked to fulfill questioner before and after following simulation training. Data were analyzed using paired t test.Results: there are improvements in the 8 basic skills of basic emergency assistance obtained by CFRs after participating in the CFR simulation. The increase in competence is not only in the number of members at a moderate level but also from a moderate level to the highest level.Conclusion: training through simulation is one of the most effective ways to increase the competence of CFR members so that they have adequate capacity as the frontline for help to minimize the risk of death and disability as long as they have not received definitive care in the hospital.